(untitled) (International Journal of Engineering and Computer Science, 2013)
From the most beginning two main fundamental technologies are necessary for the evaluation & existence of VoIP i.e. telephone most widely used as first & second is the internet. In 1870sAlexander Gram Bell and Elisha Gray invented the telephone. The Internet is first developed by ARPANET (Advanced Research Projects Agency Network) in 1967, founded by the U.S. Department of Defense in 1957. As ARPANET provide a decentralized communications network would not be interrupted by a potential global war. VoIP stand for Voice over Internet Protocol is a part of internet technologies. It is a communication Protocol that has transmission technologies for delivery of voice communications and multimedia sessions over Internet Protocol (IP) networks, such as the Internet. Other technology that is synonym of VoIP i.e. IP telephony, voice over broadband (VoBB), Internet telephony, broadband phone and broadband telephony. VoIP has been progressively more popular in recent times because of its affordability, how-ever; poor reliability and voice quality remain significant factors that limit the extensive adoption of VoIP systems. Good voice quality is a vital factor for users transiting from the Public Switched Telephone Network (PSTN) to VoIP networks. It has been seen that line delay is one of the vital factors that depreciate voice quality in VoIP systems. Numerous non-real-time algorithms have been developed to estimate different aspects of voice quality in VoIP systems. In fact there is no real-time algorithm that estimates the delay content of a VoIP discussion, which could enable to take some curative actions to improve the quality while the call is in progress. In this paper, I propose a real-time fuzzy algorithm to estimate the VoIP call Quality in VoIP networks. The results obtained that shows the algorithm is able to track and estimate VoIP System performance in real-time. This algorithm could be embedding in VoIP systems to allow operators monitors calls in real-time.